2003
DOI: 10.1002/eji.200323586
|View full text |Cite
|
Sign up to set email alerts
|

Alefacept selectively promotes NK cell‐mediated deletion of CD45R0+ human T cells

Abstract: Modulation of the immune response using immunoglobulin fusion proteins has shown great promise for clinical immunotherapy of autoimmune diseases. Alefacept is an immunoglobulin fusion protein composed of the first extracellular domain of human LFA-3 fused to the hinge, C H 2 and C H 3 domains of human IgG 1 . Alefacept has previously been reported to inhibit T cell proliferation. Here, we analyzed the effects of alefacept on lymphocytes in vitro and characterized the role of autologous NK cells in its mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 55 publications
3
38
0
2
Order By: Relevance
“…We speculate that this effect may be due in part to direct blockage of CD2 and LFA-3 on the one hand, and to the increased allogeneic NK cell activity 22 that in conjunction with the Fc end of the alefacept may induce cytotoxicity of alloreactive T cells, thus downregulating GVHD activity. 17 Another possible theory to explain the rapid response against infiltrating T cells involved in GVHD may be related to neutralization of activated Fc positive dendritic cells and inflammatory genes as shown in psoriasis 23 especially combined with the other immunosuppressive agents given for GVHD.…”
Section: Discussionmentioning
confidence: 98%
“…We speculate that this effect may be due in part to direct blockage of CD2 and LFA-3 on the one hand, and to the increased allogeneic NK cell activity 22 that in conjunction with the Fc end of the alefacept may induce cytotoxicity of alloreactive T cells, thus downregulating GVHD activity. 17 Another possible theory to explain the rapid response against infiltrating T cells involved in GVHD may be related to neutralization of activated Fc positive dendritic cells and inflammatory genes as shown in psoriasis 23 especially combined with the other immunosuppressive agents given for GVHD.…”
Section: Discussionmentioning
confidence: 98%
“…Again, we hypothesize that the effect of alefacept on GVHD is augmented by the increased allogeneic NK-cell activity, 29 which in conjunction with the Fc end of the alefacept may induce cytotoxicity of alloreactive T cells, thus downregulating GVHD activity. We conclude that on the basis of our limited experience, alefacept is a promising agent for clinical application for treatment patients with extensive cGVHD even when refractory.…”
Section: Discussionmentioning
confidence: 99%
“…The role of macrophages/ monocyte in ADCP and their FcγR has been comprehensively reviewed by Gorgon et al [84]. Studies with human purified T cells and NK cells from human peripheral blood in culture [6,11] or mixed lymphocyte reaction assay on human PBMC that are devoid of neutrophils showed FcγRI and FcγRIII but not FcγRII involved in NK cell-mediated ADCC. However, studies using transgenic mice expressing human CD2 confirmed depletion of T cells in vivo but NK cell depletion via anti-asialo GMl pretreatment did not inhibit alefacept-mediated T cell depletion in these mice.…”
Section: Alefacept In Reducing Hiv Reservoir: Challengesmentioning
confidence: 99%
“…Alefacept is effective for psoriasis and other T cell-mediated autoimmune diseases [5,[10][11][12][13][14][15][16][17][18]. Alefacept responses are noteworthy for their durability.…”
Section: Introductionmentioning
confidence: 99%